PENGEMBANGAN BUKU MATHLITE SERI SUDUT UNTUK MENINGKATKAN KOMUNIKASI MATEMATIKA SISWA KELAS IV SD: PENGEMBANGAN BUKU MATHLITE SERI SUDUT UNTUK MENINGKATKAN KOMUNIKASI MATEMATIKA SISWA KELAS IV SD - Setiawan, Yohana; Sawen, Anci (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Satya Wacana, 2022)
This is a research and development of children's literature books contained mathematics to improve the mathematical communication skills of fourth grade elementary school students. This study used five of the ten steps of Borg and Gall development combined with ADDIE development model. Product validation was carried out using Delphi technique by giving questionnaires to three validators, there were children's literature experts, material experts, and media experts. Questionnaire was also given to fourth grade elementary school students to see their respond to MathLite. The results was MathLite got 3.22, it stand in good criteria based on the assessment of three validators, so it can be said that MathLite is feasible to improve students' mathematical communication. MathLite stand in very good criteria, which is 83.93% in improving students' mathematical communication based on student responses. Penelitian ini adalah Research and Development buku sastra anak bermuatan matematika untuk meningkatkan kemampuan komunikasi matematika siswa kelas IV SD. Penelitian ini menggunakan lima dari sepuluh langkah pengembangan Borg and Gall dipadukan dengan model pengembangan ADDIE. Validasi produk dilakukan dengan teknik delphi dengan memberikan kuesioner kepada tiga validator yaitu ahli sastra anak, ahli matematika SD, dan ahli media serta kuesioner respons diberikan kepada siswa kelas IV SD. Hasil dari penelitian ini MathLite mendapat skor 3,22 berada pada kriteria Baik berdasarkan penilaian dari tiga validator, sehingga dapat dikatakan layak untuk menigkatkan komunikasi matematika siswa. MathLite berada pada kriteria sangat baik yaitu sebesar 83,93% dalam meningkatkan komunikasi matematika siswa berdasarkan respons siswa.